Evaluation of the exchange coupling between adjacent magnetic layers using time-resolved magneto-optic Kerr effect (TRMOKE). (28th June 2021) - Papusoi, C; Le, T; Admana, R; Mani, P; Desai, M
Abstract: Vertical exchange coupling between the adjacent layers of a magnetic multilayer has a strong impact on the magnetization reversal mechanism. Time-resolved magneto-optic Kerr effect (TRMOKE) is used to evaluate the vertical exchange coupling energy per unit film surface J V between two Co1− X Pt X layers denominated A ( x = 27 at. %) and B ( x = 22 at. %), separated by a CoCrRu weakly-magnetic layer denominated exchange control layer (ECL), as a function of the ECL thickness d ECL in the range of 0–5 nm. The A and B layers have perpendicular anisotropy and thicknesses d A = 7 nm and d B = 5.6 nm. For this purpose, the dependence of the acoustic magnetization oscillation frequency f AC on d ECL is measured using TRMOKE and the dependence f AC ( J V ) is theoretically assessed using two models: (a) the two-spins model (TSM) assumes a parallel orientation of spins across the thickness of each layer; (b) the chain-of-spins model (CSM) takes into account the possibility of a non-collinear orientation of spins across the thickness of the A and B layers. In the case of d ECL ≳ 1 nm corresponding to J V ≲ 1 erg cm −2, TSM and CSM offer similar J V values. Below d ECL ≊ 1 nm, CSM provides a more accurate estimate of J V than TSM which underestimates J V the more significantly the lower is d ECL .